Mice Lacking Cerebellar Cortex and Related Structures Show a Decrease in Slow-Wave Activity With Normal Non-REM Sleep Amount and Sleep Homeostasis - Fujiyama, Tomoyuki; Takenaka, Henri; Asano, Fuyuki; Miyanishi, Kazuya; Hotta-Hirashima, Noriko; Ishikawa, Yukiko; Kanno, Satomi; Seoane-Collazo, Patricia; Miwa, Hideki; Hoshino, Mikio; Yanagisawa, Masashi; Funato, Hiromasa (Frontiers in Behavioral Neuroscience, 2022)
In addition to the well-known motor control, the cerebellum has recently been implicated in memory, cognition, addiction, and social behavior. Given that the cerebellum contains more neurons than the cerebral cortex and has tight connections to the thalamus and brainstem nuclei, it is possible that the cerebellum also regulates sleep/wakefulness. However, the role of the cerebellum in sleep was unclear, since cerebellar lesion studies inevitably involved massive inflammation in the adjacent brainstem, and sleep changes in lesion studies were not consistent with each other. Here, we examine the role of the cerebellum in sleep and wakefulness using mesencephalon- and rhombomere 1-specific Ptf1a conditional knockout (Ptf1a cKO) mice, which lack the cerebellar cortex and its related structures, and exhibit ataxic gait. Ptf1a cKO mice had similar wake and non-rapid eye movement sleep (NREMS) time as control mice and showed reduced slow wave activity during wakefulness, NREMS and REMS. Ptf1a cKO mice showed a decrease in REMS time during the light phase and had increased NREMS delta power in response to 6 hours of sleep deprivation, as did control mice. Ptf1a cKO mice also had similar numbers of sleep spindles and fear memories as control mice. Thus, the cerebellum does not appear to play a major role in sleep-wake control, but may be involved in the generation of slow waves.